2020
DOI: 10.1098/rsos.201848
|View full text |Cite
|
Sign up to set email alerts
|

Virtual body ownership and its consequences for implicit racial bias are dependent on social context

Abstract: When people hold implicit biases against a group they typically engage in discriminatory behaviour against group members. In the context of the implicit racial bias of ‘White' against ‘Black' people, it has been shown several times that implicit bias is reduced after a short exposure of embodiment in a dark-skinned body in virtual reality. Embodiment usually leads to the illusion of ownership over the virtual body, irrespective of its skin colour. Previous studies have been carried out in virtual scenarios tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 67 publications
2
54
0
2
Order By: Relevance
“…Further work has shown that the reduction in implicit racial bias lasts for at least one week after the VR exposure (Banakou, Hanumanthu, & Slater, 2016). Banakou et al (2020) has replicated these results when the surrounding situation is affectively neutral or positive and also confirmed the finding of Groom et al that implicit racial bias of White against Black increases when the embodiment takes place in a situation that generates negative affect. All of the above studies have used the racial IAT as a measure of implicit bias.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Further work has shown that the reduction in implicit racial bias lasts for at least one week after the VR exposure (Banakou, Hanumanthu, & Slater, 2016). Banakou et al (2020) has replicated these results when the surrounding situation is affectively neutral or positive and also confirmed the finding of Groom et al that implicit racial bias of White against Black increases when the embodiment takes place in a situation that generates negative affect. All of the above studies have used the racial IAT as a measure of implicit bias.…”
Section: Introductionsupporting
confidence: 70%
“…Apart from the human misery this causes, including long-term psychological trauma for survivors and their families, this is perceived as an assault on the entire community, which ultimately can lead to more violence. Recent resultsfor example, (Banakou et al, 2020) -that exploit the power of Virtual Reality to give people experiences of being another person suggest that it may be possible to diminish implicit racial bias. This paper describes an experimental study that utilizes such findings in the context of police racial bias.…”
Section: Introductionmentioning
confidence: 99%
“…Despite growing interest in BT and its effects, the requirements for establishing BT with non-human bodies remain ambiguous. For one, the majority of studies testing the effects of embodiment have done so using humanoid avatars 46,51,70,71 . Second, while the style (or realism) of one's virtual body does not necessarily detract from BT 72 , morphological similarity to one's body can in uence on BT 72,73 .…”
Section: Discussion: Studymentioning
confidence: 99%
“…Although the content of the experience is virtual, the experience is "real as an experience" (Slater et al, 2020, p. 5, emphasis in original), and the emotional and cognitive after-effects, although usually beneficial, can also be harmful (Slater et al, 2020). For instance, while VR interventions may reduce implicit racial bias (Banakou et al, 2016), they may also increase it in negative contexts (Groom et al, 2009;Banakou et al, 2020), suggesting potentially non-beneficent results when using VR as an "empathy machine." Similar warnings have been issued by Sri Kalyanaraman et al (2010) who immersed participants in a simulation of the effects of schizophrenia.…”
Section: Ethicsmentioning
confidence: 99%